THE NEED INTERMODAL FOR INTEGRATION FACILITIES AT THE BANJARAYA RIVERSIDE PORT OF SOUTH KALIMANTAN PROVINCE - Sari, Vita Permata; Agustini, Hera; Tungkup, Doharman Lumban; Amanda, Monica; Utami, Dianata Gusti (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2024)
Banjaraya River Port is a river port in Banjarmasin City that serves three routes, namely Banjaraya - Sakakajang, Banjaraya - Muara Teweh, and Banjaraya - Puruk Cahu with eight ships operating. Based on the results of a field survey, no supporting facilities for intermodal integration were found, such as bus stops, sidewalks, and information boards regarding intermodal integration at Banjaraya River Port. This study aims to develop a design concept for the integration (infrastructure) of connecting and supporting Banjaraya River Port with onward transportation in order to improve transportation services. This study uses an observation method to analyze the need for intermodal integration facilities at Banjaraya River Port. The results of this study obtained that the construction of supporting facilities for intermodal integration is needed at Banjaraya River Port, namely bus stops, sidewalks, and intermodal integration information boards. From the results of this study, the output is in the form of designs and sizes that have been calculated, bus stops with a size of 7.5 mx 2 m which are adjusted based on applicable regulations, sidewalk sizes with a width of xm, height x cm with a slope of x% equipped with guilding blocks, and information boards containing information about further transportation, such as further transportation schedules, fares, and routes served. Efforts that can be made by the management are to build supporting facilities for intermodal integration needed at Banjaraya River Port.